Prognostic significance of microscopic resection margin involvement in patients with gastric carcinoma - Duraker, Nüvit (Cerrahpaşa Medical Journal, 2019)
Objectives: It is controversial whether reresection subsequent to gastrectomy is beneficial in gastric carcinoma patients with confirmed microscopic resection margin involvement. In this study, the prognostic significance of microscopic tumor involvement in resection margin in various subgroups of patients with gastric carcinoma was investigated. Methods: Three hundred and thirty-one gastric carcinoma patients who were supposed to be resected curatively were included in the study; data was collected prospectively. When postoperative histologic examination revealed tumor in the resection margins, it was termed as margin positive. Margin positive and negative patients were compared with regard to histopathologic features, mortality and overall survival. Thirty patients who died of complications were not included in survival analysis. Results: Tumor involvement in the resection margin was found in 47 (14.2%) patients. Margin positivity rates were significantly higher in tumors over 6 cm in size, in undifferentiated tumors, in tumors with vascular and perineural invasion. Early mortality rates did not differ significantly between patients with positive margin and with negative margin ( 5/47, 10.6% and 25/284, 8.8%, respectively). Considering the whole series, overall 5-year survival was 2.4% in patients with margin involvement and 32.8% in patients without margin involvement (p<0.0001). In the multivariate Cox analysis margin involvement had independent prognostic significance (p<0.001). The survival of margin positive patients was poorer than margin negative patients in both node negative (p=0.0087) and node positive (p<0.0001) groups. Margin involvement had prognostic value in subgroup with the ratio of metastatic lymph nodes to removed lymph nodes was <0.50 (p<0.0001); however margin involvement had not prognostic importance in subgroup with ratio ≥0.50. Conclusion: In patients with negative lymph nodes and metastatic lymph node ratio of less than 0.50, when microscopic margin involvement is encountered postoperatively, reresection to provide negative surgical margins should be considered in suitable patients.